Gentrification and the city at eye level. - Glaser, Meredith; Karssenberg, Hans; Laven, Jeroen (RWTH, 2013)
Gentrification is another word for transformation. Whether it's urban renewal, regeneration, modernizing, or gentrification - these are all symptoms of economic development that generate a complex process of physical, social, and structural changes in a neighborhood. Rather than going on about the broad definition and impacts of gentrification, we want to highlight one specific characteristic: the role of plinths. A plinth is the ground floor of a building. It is a building's most important part for the city at eye level. Plinths are crucial for the experience and attractiveness of the urban space, both in residential and commercial areas. Gentrification, as a form of transformation, leads to better plinths and better streets for its users; and better streets and plinths also lead to gentrification. In either pathway there is one common goal: to improve the experience of the city from the eyes of its user.
Keywords: Stadterneuerung; Stadtsanierung; Stadtquartier; Problemraum; Öffentlicher Raum; Stadtraum; Städtebau; Nutzer; Sockel; Flächennutzung; Gentrifizierung; Transformation; Benachteiligter Stadtteil; Intervention; Erdgeschoss; Sockelgeschoss; Nutzungsmischung